A internacionalização em Instituições Federais de Ensino Superior do estado do Ceará na perspectiva institucional - Teixeira, Linnik Israel Lima (2018)
Globalization from the last decades has narrowed boundaries and created interdependence among nations and organizations around the world. On higher education, globalization has contributed to the expansion of an important phenomenon: internalization of higher-education institutions (IES). Internalization- controlled by IES from developed countries, has gained a great repercussion in the Brazilian universities. It has increasingly been inserted into international, scientific-academic setting, which was pointed out by rankings performed by international organisms. According to Knight (2004), internalization represents the integration between an international/intercultural dimension upon universities’ activities. Then, this study aims to comprehend the current stage from the process of internalization of the Federal Institutions of Higher Education in Ceará, such as: Federal University of Ceará (UFC), Federal Institute of Ceará (IFCE) and the University for International Integration of the Afro- Brazilian Lusophony (UNILAB). This survey was a descriptive research, and it was applied a case study by Yin (2010) with evidence multiple and data triangulation. Interviews were needed for IFES’ managers that were into phenomenon, besides of the seeking for documents, strategies and institutional policies on the process. The results showed process of institutionalization occurs in different forms at those places. This is due to institutional mission, to the reasons, historical way, and institutional and national influences. Wherever the UFC shows a major adhesion to the international requirements required by national institutions, which has answered to standards from the foreign agents. On the other hand, internalization at IFCE is totally related to academic mobility in an activity approach; it is explained by latest graduation and post-graduation. At UNILAB, internalization is strongly guided by mission of solidarity to the Lusophony countries, which is pointed out by action of structured system. However, the technology area of this institution has internationalized itself with the foreign language countries. The heterogeneous image of internalization among the IFES of Ceará leads to conclusion on necessity of promoting policies that respect specificities of each institution. After all, they are different from the genesis, and they need harmony between internationalization and institutional identity of each organization. As future suggestions, it was advised to investigate the role and training policies of the technical- administrative workers since focus are currently on professors and students, putting aside potentialities of this relevant organizational actor.